Comparative analysis of obstetric, perinatal, and neurodevelopmental outcomes following chorionic villus sampling and amniocentesis - Kim, Nari; Joo, Eun Hui; Kim, Seoyeon; Kim, Taeho; Ahn, Eun Hee; Jung, Sang Hee; Ryu, Hyun Mee; Lee, Ji Yeon (Frontiers in Medicine, 2024)
Background: The risks of invasive prenatal tests are reported in previous studies such as miscarriage, fetal anomalies, and bleeding. However, few compare short-term and long-term outcomes between invasive tests. This study aims to investigate obstetric, perinatal, and children’s neurodevelopmental outcomes following chorionic villus sampling (CVS) or amniocentesis in singleton pregnancy. Methods: This retrospective cohort study included healthy singleton pregnancies underwent transabdominal CVS (gestational age [GA] at 10-13 weeks) or amniocentesis (GA at 15-21 weeks) at a single medical center between 2012 and 2022. Only cases with normal genetic results were eligible. Short-term and long-term neurodevelopmental outcomes were evaluated. Results: The study included 200 CVS cases and 498 amniocentesis cases. No significant differences were found in body mass index, parities, previous preterm birth, conception method, and cervical length (CL) before an invasive test between the groups. Rates of preterm labor, preterm premature rupture of the membranes, preterm birth, neonatal survival, neonatal short-term morbidities, and long-term neurodevelopmental delay were similar. However, the CVS group had a higher rate of cervical cerclage due to short CL before 24 weeks (7.0%) compared to the amniocentesis group (2.4%). CVS markedly increased the risk of cervical cerclage due to short CL (adjusted odd ratio [aOR]=3.17, 95%CI [1.23-8.12], p=0.016), after considering maternal characteristics. Conclusion: Performing CVS resulted in a higher incidence of cerclage due to short cervix or cervical dilatation compared to amniocentesis in singleton pregnancies. This highlights the importance of cautious selection for CVS and the necessity of informing women about the associated risks beforehand.